Subscapular Abscess Caused by Panton-Valentine Leukocidin-Positive Staphylococcus aureus: An Atypical Presentation - Kamal Patel; Emma Spowart; Dana Sochorova; Nadia Diego; Georgios Mamarelis; Mohammad Zain Sohail (Case Reports in Orthopedics)
Subscapular abscess is an uncommon condition which requires early recognition followed by prompt surgical intervention. We present a case of spontaneous subscapular abscess following blunt trauma to the shoulder in a patient with a history of recurrent superficial soft tissue infections, in which Panton-Valentine leukocidin-producing S. aureus was identified as the infectious agent. This strain due to its virulence can lead to fatal infections in otherwise healthy individuals; therefore, a high index of suspicion is needed to investigate with an MRI to rule out abscess formation in a patient with acute shoulder girdle pain and negative joint aspirate. Urgent surgical intervention and targeted antimicrobial therapy against PVL-positive S. aureus in accordance with microbiologist yield good outcomes.